Single-Stage Coverage of Exposed Critical Structures With Intact Decellularized Fish Skin and Simultaneous Epidermal Autograft Application: The “Sandwich” Technique - Katherine C. Benedict, MD; John M. Sullivan, MD; Laura I. Galarza, MD; Marc E. Walker, MD, MBA (Journal of Hand Surgery Global Online)
Coverage of exposed tendon and bone in upper-extremity injuries presents a reconstructive challenge, often requiring staged procedures or complex microsurgical reconstruction techniques. We present a case series using a single-stage approach with intact decellularized fish skin graft laminated with a simultaneous split-thickness skin autograft. This technique aims to reduce the number of surgeries and decrease time to complete healing. Two cases are reported: a dog-bite forearm injury with exposed extensor tendons devoid of peritenon and a work-related crush injury of the hand with exposed metacarpal fracture. Following definitive debridement, both cases ultimately achieved successful wound healing with simultaneous placement of decellularized fish skin graft laminated with split-thickness skin autograft without further interventions.